Hb G Makassar (beta 6 : Glu→Ala) in a Thai Family - Siripakorn Sangkitporn (2018)
Hemoglobin G Makassar was identified in a family of Thai origin, which was found to share identical properties with hemoglobin S in routine hemoglobin separation both by cellulose acetate electrophoresis and cation-exchange HPLC. It is, therefore, subjects with hemoglobin G Makassar and hemoglobin S who may sometimes be mistakenly identified for each other. In this study, identification of hemoglobin G Makassar was achieved by DNA sequence analysis, which revealed a single nucleotide substitution GAG→GCG at codon 6 of the beta-globin gene. The hemoglobin variant was hemoglobin G Makassar [beta 6 : Glu→Ala]. This is the first report of hemoglobin G Makassar in Thailand.